Synthesizing hybrid copper phosphate (Cu3(PO4)2) nanoflowers using Cu+2 and shed snakeskin: antioxidant, antibacterial, anticancer, guaiacol, anionic, and cationic dye degradation properties - Cagri Caglar Sinmez; Fatih Doğan Koca (Journal of Biological Engineering)
Abstract Background Synthesis of organic@inorganic hNFs is achieved by the coordination of organic compounds containing amine, amide, and diol groups with bivalent metals. The use of bio-extracts containing these functional groups instead of expensive organic inputs such as DNA, enzymes, and protein creates advantages in terms of cost and applicability. In this study, the application potentials (antioxidant, antibacterial, anticancer, guaiacol, anionic, and cationic dye degradation) of hybrid (organic@inorganic) nanoflowers (hNFs) synthesized with Cu+2 and snakeskin (SSS) were proposed. Results Morphology, presence, and composition of elements of Cu and SSS-coordinated hNFs (Cu@SSS hNFs) were shown through FE-SEM–EDX spectroscopy. According to FE-SEM findings, hNFs synthesized with 0.5 ml and 1 ml extract have diameters of 12.81 and 3 µm, respectively. Diffraction peaks of hNFs determined by XRD were consistent with JCPDS Card 00–022 –0548. Cu@SSS NFs showed antioxidant properties depending on time through DPPH scavenging behavior (ability (R2: 0.5612, IC50: 2.07 mg/ml). Cu@SSS hNFs synthesized coordination of SSS and Cu degraded (75%) methylene blue at the highest pH 9 condition. However, hNFs highest degraded (68%) brilliant blue in an acidic PBS medium. hNFs oxidized guaiacol depending on exposure time. Cu@SSS hNFs demonstrated antibacterial properties towards Gram (-/ +) pathogen strains (MIC: 60 µg/ml). The catalytic and antimicrobial properties of hNFs were mentioned by the Fenton reaction. The cytotoxicity of Cu@SSS hNFs on the lung carcinoma (A549) cell line was shown to be concentration-dependent by the MTT test assay (IC50: 56.4 µg/ml). Conclusion As a result, Cu-based hNFs synthesized by using an organic waste (SSS) might be improved for environmental and biomedical applications.